An Effective Approach of Nanoscale CaF2 Addition into ZTA Composite to Enhance Tribological Characteristics in Dry Sliding. Issue 1 (2nd January 2021) - Mazumder, Subhrojyoti; Sadhu, Kishor Kumar; Ghosh, Kunal; Roy, Poulomi; Mandal, Nilrudra
ABSTRACT: This work was carried out to establish a noble technique to enhance tribological characteristics of zirconia toughened alumina (ZTA) ceramic composite by adding 10 wt% nano CaF2 (∼50 nm) via chemical co-precipitation method. Result of the tribological tests, carried out using ball-on-disk tribo-pair in dry sliding, showed a considerable improvement in coefficient of friction up to ∼55% and the wear rate ∼35% in CaF2 /ZTA composite as compared to pure ZTA composite fabricated via chemical processing route followed by hot pressing. In the later stage, a similar CaF2 /ZTA ceramic composite was fabricated by traditional physical mixing process of commercial CaF2 and ZTA powders followed by hot pressing using the same parameters and the tribological performances were compared. The specimen fabricated via chemical route possessed better responses in terms of tribo-mechanical behaviors as compared to the specimen fabricated via traditional mixing. Various phases of the composites were examined by X-ray diffraction. Elemental distribution and the worn surface were characterized by energy dispersive X-ray analysis and field emission scanning electron microscopy, respectively. GRAPHICAL ABSTRACT: